2001
DOI: 10.1046/j.0022-0477.2001.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precipitation and species composition on phytomass of a semi‐arid African grassland

Abstract: Summary 1The influence of botanical composition on annual phytomass production of a semiarid grassland in response to precipitation was tested with a 19-year experiment. Three compositional states reflecting good, medium and poor rangeland condition, whose basal cover increased from poor through to good, were created in 1978.2 Multiple regression models were developed for assessing whether phytomass was influenced by precipitation, composition, phytomass of the previous year, basal cover, abundance of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
167
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 40 publications
(72 reference statements)
16
167
4
Order By: Relevance
“…in the recent decades (Zhou et al, 2002;Bai et al, 2004;Zhou et al, 2006). Many researches indicated that drought and the seasonal precipitation seriously affect the growth and the community composition of grasslands (Distel et al, 1996;O'connor et al, 2001;Kröpfl et al, 2002;Wang and Gao, 2003), and drought is particularly a problem, occurring episodically in many regions (Kang et al, 2002;Shah and Paulsen, 2003). The global climatic change may result in not only the change of total precipitation but also the occurrence of discontinuous drought.…”
mentioning
confidence: 99%
“…in the recent decades (Zhou et al, 2002;Bai et al, 2004;Zhou et al, 2006). Many researches indicated that drought and the seasonal precipitation seriously affect the growth and the community composition of grasslands (Distel et al, 1996;O'connor et al, 2001;Kröpfl et al, 2002;Wang and Gao, 2003), and drought is particularly a problem, occurring episodically in many regions (Kang et al, 2002;Shah and Paulsen, 2003). The global climatic change may result in not only the change of total precipitation but also the occurrence of discontinuous drought.…”
mentioning
confidence: 99%
“…approaches that seem reasonable but have severe limitations, particularly when applied to large areas: visual assessment of satellite imagery is entirely subjective and therefore unrepeatable; field surveys, such as the National Resources Inventory (Nusser and Goebel, 1997), are limited to small areas (Budde et al, 2004;O'Connor et al, 2001;Prince, 2004) that can be assessed by an evaluator on the ground; and process modeling of potential production followed by comparison with actual production (Bai et al, 2008;Boer and Puigdefabregas, 2005) suffers from the need for data and parameters that are generally not available (Prince, 2002).…”
mentioning
confidence: 99%
“…As for most of Sub Saharan Africa's drylands, with the possible exception of South Africa (e.g. O'Connor et al 2001), there is a general lack of data required to model the impacts of climate change on the local dryland production system. These data constraints restrict the level of detail that can be incorporated in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The right hand part of the equation shows how the long-term grazing pressure affects the rain-use efficiency by moving the curve towards a lower rain-use efficiency, while maintaining a quadratic relation (cf. O'Connor et al 2001). Further explanation of the function is provided in Hein and De Ridder (2006) and Hein and Weikard (2004).…”
Section: Input Variablesmentioning
confidence: 99%
See 1 more Smart Citation